DESAIN SISTEM INTELEJENSIA BISNIS PADA RANTAI PASOK PRODUK JAMU BERBASIS PENTAHO BUSINESS INTELLIGENCE - Aster Aryati; Dian Anwar (Politeknik APP Jakarta, 2017)
This paper designs business intelligence system for supply chain of herbal products in Indonesia. System design is done with system entity approach to obtain system attributes, conceptual system design using Businees Process Modeling Notation (BPMN) 2.0 and unified modeling language (UML) and finally integrated with pentaho business intelligence suite suite including integration and business analytics data. The result of business intelligence system design is able to transform raw data into information and mengintrpertasikannya in the form of a visual supply chain herbal products for the purposes of identification, development and create new business strategy opportunities.